If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 5p = 5.2 Solving 2b + 5p = 5.2 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5p' to each side of the equation. 2b + 5p + -5p = 5.2 + -5p Combine like terms: 5p + -5p = 0 2b + 0 = 5.2 + -5p 2b = 5.2 + -5p Divide each side by '2'. b = 2.6 + -2.5p Simplifying b = 2.6 + -2.5p
| 3(x-4)+68=-4 | | -r+1=-7+4r-r | | 2(3x-13)=-20 | | 3(c+2+1)=9c+3 | | 86=5x-14 | | y+6-4y-3=-30 | | 1-n=13-4n | | -5(x+3)(x+8)= | | 9x^2-18w+24=0 | | 30c=18360 | | 2(1-16a)=-2a-6(a-7) | | 6x+11=8x+13 | | 3k-7k=-9-k | | 27=2y-13 | | -(-9-6x-6y)= | | 980+n=1020 | | E=(8) | | -5=3x+8 | | -4x+8=-12+x-8-7 | | -(4x-10)+2(3x+15)= | | 4x^3+24x^2+12x-40=0 | | 6x-3y+14w-5y-4w+9x= | | 592=2L+2(5L+6) | | 2(-1)+9= | | 12x+9=9x-18 | | 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 | | 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 | | 5(3x-7)-(3x+9)= |